STRATEGI PEMULIHAN UMKM DI KABUPATEN SUMBAWA PASCA MASA PANDEMI COVID-19 - Fadli Alhindoan; Roos Nana Sucihati; Elly Karmeli (Jurnal Ekonomi & Bisnis, 2023)
This study aims to determine the strategy of MSMEs in Sumbawa Regency in increasing sales volume during the Covid-19 pandemic. This research uses a descriptive method with a qualitative approach. The type of data used is qualitative which is obtained directly from primary sources using interview techniques. The informants in this study were all people involved in the daily operations of Rizka Shop, which consisted of business owners, store employees, and consumers. Data analysis in this study uses the SWOT analysis technique to formulate various alternative strategies to increase MSME sales volume during the Covid-19 pandemic. This analysis is based on logic that can maximize strengths and opportunities, but at the same time minimize weaknesses and threats. The results showed that the SWOT analysis in increasing the sales volume of the Rizka Shop Sumbawa Besar Store during the Covid-19 pandemic resulted in four alternative strategies, namely the SO strategy, the WO strategy, the ST strategy and the WT strategy. The alternative development strategies resulting from this research are improving service quality to maintain the store's image to remain good, conducting promotions and sales by utilizing technological developments, increasing the variety of products sold, creating uniqueness that characterizes the store, sell products according to the needs and desires of the market and consumers, and selling products from well-known brands or brands.